Co-registered Geochemistry and Metatranscriptomics Reveal Unexpected Distributions of Microbial Activity within a Hydrothermal Vent Field - Olins, Heather C.; Rogers, Daniel R.; Preston, Christina; Ussler, William; Pargett, Douglas; Jensen, Scott; Roman, Brent; Birch, James M.; Scholin, Christopher A.; Haroon, M. Fauzi; Girguis, Peter R. (Frontiers in Microbiology, 2017)
Despite years of research into microbial activity at diffuse flow hydrothermal vents, the extent of microbial niche diversity in these settings is not known. To better understand the relationship between microbial activity and the associated physical and geochemical conditions, we obtained co-registered metatranscriptomic and geochemical data from a variety of different fluid regimes within the ASHES vent field on the Juan de Fuca Ridge. Microbial activity in the majority of the cool and warm fluids sampled was dominated by a population of Gammaproteobacteria (likely sulfur oxidizers) that appear to thrive in a variety of chemically distinct fluids. Only the warmest, most hydrothermally-influenced flows were dominated by active populations of canonically vent-endemic Epsilonproteobacteria. These data suggest that the Gammaproteobacteria collected during this study may be generalists, capable of thriving over a broader range of geochemical conditions than the Epsilonproteobacteria. Notably, the apparent metabolic activity of the Gammaproteobacteria—particularly carbon fixation—in the seawater found between discrete fluid flows (the intra-field water) suggests that this area within the Axial caldera is a highly productive, and previously overlooked, habitat. By extension, our findings suggest that analogous, diffuse flow fields may be similarly productive and thus constitute a very important and underappreciated aspect of deep-sea biogeochemical cycling that is occurring at the global scale.